New Pycnomerus Erichson (Coleoptera: Zopheridae: Pycnomerini) from Rimatara, French Polynesia - Porch, Nick; Smith, Tessa R. (Zootaxa, 2017)
We describe two species of Pycnomerus, P. rimatara and P. prebblei, using subfossil material, from the island of Rimatara in the Austral Archipelago of French Polynesia. We consider it likely that these species are globally extinct, a result of the combination of a range of factors including: their probable single island endemic status, the lack of intact indigenous forest on Rimatara, their occurrence in the subfossil record only in samples older than 200–300 years before the present, and lack of historical collections. The potential extinction of these species reflects the long history of human transformation of Polynesian lowland forest habitats, especially the use of fire to transform landscapes, and parallels extensive and well-known extinctions in birds and land snails.